Physical, structural, optical and gamma radiation attenuation properties of germanate-tellurite glasses for shielding applications - Kaky, Kawa M.; Sayyed, M. I.; Mhareb, M. H. A.; Abdalsalam, Alyaa H.; Mahmoud, K. A.; Omar Baki, Sharudin; Mahdi, Mohd Adzir (Elsevier, 2020)
Germanate-tellurite glasses with a composition of (75-x) TeO2-xGeO2–12.5ZnO-12.5BaO, where x = 0, 5, 10, and 20 mol%, were synthesized. A traditional melt-quenching-annealing process was used to fabricate these glasses, at 1000 °C for melting and 300 °C for five hours for annealing. X-ray diffraction was used to investigate the structural features of each sample between 10 °C and 80 °C to prove the amorphous nature of these glasses. Moreover, Attenuated Total Reflectance Fourier Transform Infrared (ATR-FTIR) was employed to explore the functional groups of Te, Ge, and other elements. To study the transparency, cut-off wavelength, and other optical properties of the glasses, such as indirect, direct, and Urbach energy band gaps, optical absorption was measured in the range of 200–800 nm. Additionally, the radiation shielding properties for the germanium based-tellurite glasses were calculated using Monte Carlo N particle transport code (MCNP-5). The simulated results were compared with XCOM software and the results between the two methods closely agreed. The maximum mass attenuation coefficient varied between 47.305 and 50.620 cm2.g − 1 for TG1 and TG4 glasses respectively at 0.015 MeV. The effective atomic number (Zeff) for the prepared germanium based-tellurite glasses was evaluated and the results revealed that the maximum Zeff values were found at 0.04 MeV, varying between 48.24 and 49.98 for TG4 and TG1.